Cryogenic pipe flow simulation for liquid nitrogen - Lim, Chong Lye; Kamarul Arifin, Ahmad; Ahmedov, Anvarjon A.; N. M., Adam (UiTM Press, 2017)
Cryogenics is dealing with very low temperatures of less than 120 K. Applications of cryogenic can be found in variety of fields such as physics, chemistry, biology, medicine, engineering and industry. Cryogenic pipe flow is very different compared to normal fluid pipe flow in terms of evaluation and analysis in terms of fluid state change caused by heat leak in cryogenics during transportation in transfer line. The present study is on liquid nitrogen pipe flow simulation in order to understand the flow characteristic and temperature distribution in the pipe flow. Computational fluid dynamics (CFD) software has been employed for the present study. The 3-dimensional liquid nitrogen pipe flow simulation has been conducted using ANSYS FLUENT to obtain the flow characteristic and temperature distribution. The turbulent liquid nitrogen pipe flow has been simulated and the flow velocity and the temperature distribution have been obtained. As a result from the simulation, the temperature distribution shows the temperature of the flow exceeds the normal boiling point of liquid nitrogen (77.347 K) and this leads to state changing from liquid to vapour and turning the flow into two phase flow. In order to have the desired flow velocity of less than 1 m/s for pipe size of 22.1 mm inner diameter and 1 m length, the inlet volume flow rate should not be more than 500 LPH (litre per hour) as per simulation results.